SOLUTION OF PRACTICAL PROBLEMS IN PRACTICAL PHYSICS LESSONS IN ACADEMIC LYCEUMS - M. Sh. Mirzaev (The Conference Hub, 2025)
The article describes the specific aspects of organizing practical training classes in physics for academic lyceum students. In the future, most of the graduates will choose natural and concrete and technical sciences. Therefore, the need and ways to prepare graduates to learn physics in technical higher education institutions have already been shown.
Keywords: organization of practical lessons in physics, academic lyceum students, formulation and solution of physics problems and comparison with table values.